2020
DOI: 10.1186/s13104-020-05223-x
|View full text |Cite
|
Sign up to set email alerts
|

Two years study of prevalence and antibiotic resistance pattern of Gram-negative bacteria isolated from surgical site infections in the North of Iran

Abstract: Objective: The present study aimed to investigate the frequency and antibiotic susceptibility pattern of Gram-negative bacteria (GNB) isolated from surgical site infections (SSIs) in the North of Iran. Results: This cross-sectional study conducted over a two-year period during 2018-2020 on all cases of SSIs who had a positive culture for a GNB. Standard microbiological tests were followed for the bacterial isolation and identification. Antimicrobial susceptibility profiles were determined using disk diffusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 34 publications
2
11
0
Order By: Relevance
“…In addition, E . coli was the most frequent pathogen, which is consistent with other studies [ 28 , 29 ]. The results of antibiogram test for 497 bacterial isolates recovered from patients revealed that amikacin and imipenem were the most effective antimicrobials against the strains.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, E . coli was the most frequent pathogen, which is consistent with other studies [ 28 , 29 ]. The results of antibiogram test for 497 bacterial isolates recovered from patients revealed that amikacin and imipenem were the most effective antimicrobials against the strains.…”
Section: Discussionsupporting
confidence: 92%
“…Overall, 61% of isolates were MDR. In a similar study performed in the north of Iran, a remarkable rate of MDR isolates (62.8%) was found, which displayed an increasing trend [ 28 ]. The MDR prevalence in Asia is 50% [ 33 ], very high in Saudi Arabia [ 34 ], and 13% in India [ 35 ].…”
Section: Discussionmentioning
confidence: 98%
“…The prevalence of MDR was 45.2% which is much lower than the study conducted at the Ethiopian Public Health Institute by Beyene et al 94.5% [ 37 ], three referral hospitals, Ethiopia by Moges et al 85.8% [ 43 ], Felegehiwot Hospital, Ethiopia by Moges et al 80% and by Alebel et al 81.1% [ 44 , 48 ], Addis Ababa, Ethiopia by Teklu et al 68.3% [ 49 ], northern Iran by Hemmati 62.8% [ 50 ], and Jimma Medical Center, Ethiopia by Biset et al 56.67% [ 51 ]. The variation might be due to the study population, the number of isolates assessed or the test method utilized.…”
Section: Discussionmentioning
confidence: 87%
“…The dominant carbapenemase-producing gram-negative bacilli were Klebsiella Pneumoniae 8.3%[9/109] followed by Acinetobacter species 6.8% [5/74], the study results marginally coincides with the findings of the following researchers which demonstrated the dominant prevalence of carbapenemase-producing Klebsiella pneumoniae: Beyene et al Klebsiella pneumoniae 5.6% [19], Melese et al Klebsiella pneumoniae 10.5%[24], Moges et al Klebsiella pneumoniae 5.8%[25], Moges et al Klebsiella pneumoniae 10.1%[26], Lopez-Hernandez Klebsiella pneumoniae 45% [29].The present study disagrees with finding by Okoche et al, which showed E. coli as the highest carbapenemase-producing organisms[28], The discrepancy could be explained by the fact that they utilized Boronic acid-based inhibition, a modified Hodge and EDTA double combination disk test, the number of samples analyzed, and a different geographical location. , etc.The highest number of carbapenemase producing isolates were recovered from urine samples 13/23(56.5%), which strongly disagrees with the results of study conducted by Moges et al in which the highest number of carbapenemase producing isolates was recovered from blood samples 22/24(91.6%)[25],The prevalence of MDR was 45.2% which is much lower than the study conducted at Ethiopian Public Health Institute, Ethiopia by Beyene et al 94.5%[19], three referral hospitals, Ethiopia by Moges et al 85.8%[25], Felegehiwot Hospital, Ethiopia by Moges et al 80% and by Alebel et al 81.1%[26,30], Addis Ababa, Ethiopia by Teklu et al 68.3%[31], North Iran by Hemmati 62.8%[32], and Jimma medical center, Ethiopia by Biset et al 56.67%[33]. The variation might be due to the study population, the number of isolates assessed, the technique utilized, etc.…”
mentioning
confidence: 70%